Relations, relationships and relatedness: residential child care and the family metaphor. Issue 1 (3rd January 2013) - Kendrick, Andrew
Abstract Residential care has had a poor reputation. There are concerns about the abuse of children in care, and evidence of poor outcomes and poor practice. In this context, residential care is often compared in a negative way to family placements. On the other hand, residential care can also provide a positive experience for some children and young people. Residential care has increasingly been contrasted with family placements, and yet children and young people describe their positive experiences in residential care as like being in a family, and refer to care staff using kin terms, such as 'dad' or 'sister'. With the growing diversity of families in Western society, there have been significant developments in sociological theories of families, and these highlight the importance of family practices and displaying family. New kinship studies in anthropology have raised questions about the nature of the family. Research on children's conceptualization of family has begun to identify features of 'family‐like' relationships. These theories will be discussed in relation to the ambivalence about residential care, current thinking about residential child care and, importantly, the way in which some children and young people use the family metaphor to express their experience. The paper will explore the ways in which this can develop and benefit practice in residential care.